UPAYA GURU DALAM MENINGKATKAN KEDISIPLINAN SISWA TINGKAT SEKOLAH DASAR MELALUI PENERAPAN PERATURAN DAN PROSEDUR KELAS - Risnawati Munte; Wiputra Cendana (COLLASE (Creative of Learning Students Elementary Education), 2022)
In the development of student character formation, educators are needed to facilitate student discipline. Based on the facts of the problems found, there are some student behaviors that are less disciplined during learning. The violation committed is not complying with the mutually agreed rules. The purpose of this paper is to determine the effect of applying rules and procedures on the formation of elementary school students' discipline in learning that takes place in the classroom, through qualitative descriptive research methods. The application of rules and procedures applied in the classroom can be carried out consistently with the aim of familiarizing students with order. Through this, discipline will be formed in students. Based on the facts, when conducting research at an elementary school in Lampung, the authors found that the consistent application of rules and procedures had a positive effect on changes in student behavior. In conclusion, the use of classroom rules and procedures can improve student discipline behavior if it is carried out consistently and repeatedly in the classroom. Suggestions for teachers in the future are to continue to apply classroom rules and procedures consistently and give warnings or remind students if they violate applicable rules and procedures